FACTOR ANALYSIS OF FRAUD CAUSES BY THE PERCEPTION OF AUDITORS IN THE PROVINCE OF NORTH SULAWESI - Lambris, Didi Ronald; Lengkong, Victor P.K. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Fraud is defined as foul or scam in finance, Â which is not only problems faced by businesses and industries, but also haunts the implementation of government conduct around the world, also in Indonesia. The data by KPK shows Indonesian corruption cases from 2011 to 2014 (as of October 31, 2014). The perpetrators of corruption based on positions are as many as 193 actors, based on the type of case as many as 207 cases, and as many as 206 cases based agencies. In North Sulawesi, according to data Corruption Court Class 1 A, the number of cases of Corruption during 2011 to October 2014 are as many as 125 cases. The purpose of this research is to identify and analyze the factors that cause the perception of fraud according to the auditor. This study used 105 respondents by the Judgement sampling technique and exploratory factor analysis method was used. The results shows greed and fear of losing office factors does not determine the occurrence of fraud. There are five new factor determinants of fraud that are classified as individual behavior, lack of supervision, lack of attention boss, financial pressures and working comfort factors. Role of synergy between the Internal Auditor, Independent Auditor, Government Auditor and Tax Auditor with the Government and leaders of the business community and local government in North Sulawesi province is expected to prevent fraud by making fraud prevention action plan.Â  Keywords: fraud, perception, auditor